Challenging heteronormative scripts through film and transformative pedagogy among TVET college students - Ngidi, N.D.; Dlamini, M.A.C. (South African Journal of Higher Education, 2017)
We describe an initiative aimed at addressing homophobia and destabilising heteronormativity in higher education. The initiative was implemented in 2014 at a Technical Vocational Education and Training (TVET) college in KwaZulu-Natal (KZN) and involved 20 newly formed peer educators and one lecturer from the college. We focussed on work which emphasised the creation of a safe and welcoming environment for gender non-conforming students. In particular, we made use of film and transformative pedagogy to address homophobia at the TVET college. Through analysing the participants’ reflections we found evidence that the intervention facilitated students’ critical thinking and self-examination, while helping them find alternative ways of bringing about social change and gender equity in their ‘day-to-day praxis’. The initiative further provided space to forge new ways of talking about and addressing abuse of LGBTI students; thus enabling an appreciation of the resourcefulness of film. Overall we highlight the potential value of film and transformative pedagogy in addressing homophobia and disturbing heteronormativity among students in a TVET college.